2017
DOI: 10.1038/s41598-017-15911-7
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome assembly of Zanthoxylum bungeanum using Illumina sequencing for evolutionary analysis and simple sequence repeat marker development

Abstract: Zanthoxylum, an ancient economic crop in Asia, has a satisfying aromatic taste and immense medicinal values. A lack of genomic information and genetic markers has limited the evolutionary analysis and genetic improvement of Zanthoxylum species and their close relatives. To better understand the evolution, domestication, and divergence of Zanthoxylum, we present a de novo transcriptome analysis of an elite cultivar of Z. bungeanum using Illumina sequencing; we then developed simple sequence repeat markers for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 49 publications
(47 reference statements)
7
35
0
1
Order By: Relevance
“…Among the mononucleotide repeats, A/T repeats (95.08%) were far more prevalent than G/C repeats (4.92%), which was consistent with most plants (Gao et al, 2013;Yue et al, 2016;Feng et al, 2017;Taheri et al, 2019). The most abundant dinucleotide repeat was the AC/GT motif (65.37%), followed by AG/CT (22.93%) and AT/TA (10.73%), which was similar to previous findings in other Chrysanthemum species Chrysanthemum indicum (Han et al, 2018).…”
Section: Figure 4 | Results Of the Bayesian Clustering Analysis Condusupporting
confidence: 87%
“…Among the mononucleotide repeats, A/T repeats (95.08%) were far more prevalent than G/C repeats (4.92%), which was consistent with most plants (Gao et al, 2013;Yue et al, 2016;Feng et al, 2017;Taheri et al, 2019). The most abundant dinucleotide repeat was the AC/GT motif (65.37%), followed by AG/CT (22.93%) and AT/TA (10.73%), which was similar to previous findings in other Chrysanthemum species Chrysanthemum indicum (Han et al, 2018).…”
Section: Figure 4 | Results Of the Bayesian Clustering Analysis Condusupporting
confidence: 87%
“…In fact, both Citrus and Zanthoxylum belong to Rutaceae [25]. The consistent results indicated that Zanthoxylum is a relatively recent species that is predicted to have diverged from Citrus 36.5-37.7 million years ago [1,26].…”
Section: Discussionmentioning
confidence: 67%
“…In summary, a large number of molecular markers were detected in the present study, indicating that high variation might exist in Z. armatum. In a previous study, 11 pairs of primers were used to clearly distinguish Zanthoxylum bungeanum (red Sichuan pepper) from Zanthoxylum armatum (green Sichuan pepper), even differentiating various cultivars [1]. The molecular markers screened in the present study provide rich information and could contribute to the improvement of a molecular marker database that can be used for revealing high polymorphism and multiple alleles and for markerassisted selection breeding in Zanthoxylum species.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Of the 123 567 unigenes, 75.65% were between 201 and 500 bp and 3.04% (4971) of the unigenes were longer than 2000 bp ( Table 2). The data size and unigene number were much larger than a previous study 31 , which generated a more comprehensive transcriptome of Z. bungeanum pericarps.…”
Section: Sequencing and De Novo Assemblymentioning
confidence: 98%